2019
DOI: 10.1523/jneurosci.1985-18.2019
|View full text |Cite|
|
Sign up to set email alerts
|

Hyper-excitability and hyper-plasticity disrupt cerebellar signal transfer in the IB2 KO mouse model of autism

Abstract: Autism spectrum disorders (ASDs) are pervasive neurodevelopmental conditions that often involve mutations affecting synaptic mechanisms. Recently, the involvement of cerebellum in ASDs has been suggested, but the underlying functional alterations remained obscure. We investigated single-neuron and microcircuit properties in IB2 (Islet Brain-2) KO mice of either sex. The IB2 gene (chr22q13.3 terminal region) deletion occurs in virtually all cases of Phelan-McDermid syndrome, causing autistic symptoms and a seve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 119 publications
2
30
0
Order By: Relevance
“…The functional relevance of this inhibitory organization has recently been described through multi-electrode array recordings and voltage-sensitive dye imaging (Mapelli and D’Angelo, 2007; Mapelli et al, 2009; D’Angelo et al, 2013). Previous investigations in vitro have shown that lateral inhibition in the GL originates a center-surround organization of granule cell activity (Mapelli and D’Angelo, 2007; D’Angelo, 2008; Soda et al, 2019), characterized by prevailing excitation in the core, surrounded by an inhibited area. The center-surround pattern is generated as follows: when the MFs discharge in bursts, both granule cells and Golgi cells are activated in the same region.…”
Section: Cerebellar Interneurons Functional Connectivitymentioning
confidence: 97%
See 1 more Smart Citation
“…The functional relevance of this inhibitory organization has recently been described through multi-electrode array recordings and voltage-sensitive dye imaging (Mapelli and D’Angelo, 2007; Mapelli et al, 2009; D’Angelo et al, 2013). Previous investigations in vitro have shown that lateral inhibition in the GL originates a center-surround organization of granule cell activity (Mapelli and D’Angelo, 2007; D’Angelo, 2008; Soda et al, 2019), characterized by prevailing excitation in the core, surrounded by an inhibited area. The center-surround pattern is generated as follows: when the MFs discharge in bursts, both granule cells and Golgi cells are activated in the same region.…”
Section: Cerebellar Interneurons Functional Connectivitymentioning
confidence: 97%
“…The result is LTP in the center and LTD in the surround, so that LTP and LTD assume a center-surround organization. Modified from Soda et al (2019). (b) MLIs provide the substrate for lateral inhibition of PCs by virtue of the orthogonal arrangement of excitation and inhibition onto PCs: the PFs run coronally, whereas the axons of MLIs run sagittally.…”
Section: Cerebellar Interneurons Functional Connectivitymentioning
confidence: 99%
“…Recent anatomical, structural and functional evidence has revealed that cerebellar activation is associated with addiction, social cognition and emotional processing [90][91][92][93]. Furthermore, cerebellar lesions are implicated in cognitive disorders and abnormal social behavior such as in autism spectrum disorders (ASD), cognitive affective syndrome, schizophrenia and epilepsy [93][94][95][96][97][98][99][100]. Notably, ASD patients report both motor dysfunctions together with non-motor symptoms, suggesting that cerebellar impairment might indeed contribute to both [95,100,101], likely depending on the connected brain areas [102].…”
Section: Non-sensorimotor Functionsmentioning
confidence: 99%
“…Furthermore, cerebellar lesions are implicated in cognitive disorders and abnormal social behavior such as in autism spectrum disorders (ASD), cognitive affective syndrome, schizophrenia and epilepsy [93][94][95][96][97][98][99][100]. Notably, ASD patients report both motor dysfunctions together with non-motor symptoms, suggesting that cerebellar impairment might indeed contribute to both [95,100,101], likely depending on the connected brain areas [102]. In non-human primates, tract-tracing investigations have demonstrated that topographically distinct regions (called output channels) of the DCN project to different cortical areas: with dorsal parts sending efferent fibers to the motor cortex and ventral parts to the prefrontal and parietal cortexes, which are generally involved in cognitive and higher-order executive functions [103,104].…”
Section: Non-sensorimotor Functionsmentioning
confidence: 99%
“…Adding another layer of complexity, a mouse model of Phelan-McDermid syndrome causing autistic phenotypes with a deficiency of mitogen-activated protein kinase 8 interacting protein 2 (MAPK8IP2/IB2), which plays an important role in regulating the ratio of AMPARs to NMDARs at glutamate synapses, revealed no synaptic ultrastructure alterations of cerebellar glutamatergic synapses and featured normal synaptic clefts and postsynaptic densities and abundant presynaptic vesicles [252]. However, despite the normal ultrastructure, a larger NMDAR-mediated current and enhanced intrinsic excitability and LTP were revealed in this mouse model [253].…”
Section: Autism Spectrum Disordermentioning
confidence: 83%